2012
DOI: 10.1016/j.tjog.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes according to increasing maternal age

Abstract: Increasing maternal age is an independent and substantial risk factor for adverse perinatal and obstetric outcomes. These adverse outcomes become more common as increasing maternal age without a clear cutoff age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
55
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 17 publications
11
55
3
5
Order By: Relevance
“…S. Muganyizi, B. Balandya / Open Journal of Obstetrics and Gynecology 3 (2013) 51-57 52 design problem. Some studies treat the age below 20 years as generally risky for obstetric complications [4,[6][7][8][11][12][13] while others hold that older teenagers (17 -18 years) have comparable outcomes to low risk controls [2,14,15]. The arbitrary assignment of heterogeneous age groups as risky or as controls may seriously interfere with the interpretation of results.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Muganyizi, B. Balandya / Open Journal of Obstetrics and Gynecology 3 (2013) 51-57 52 design problem. Some studies treat the age below 20 years as generally risky for obstetric complications [4,[6][7][8][11][12][13] while others hold that older teenagers (17 -18 years) have comparable outcomes to low risk controls [2,14,15]. The arbitrary assignment of heterogeneous age groups as risky or as controls may seriously interfere with the interpretation of results.…”
Section: Open Accessmentioning
confidence: 99%
“…For older women, poor obstetric outcomes are frequently attributed to increased risk of genetic and medical disorders. Although many studies have reported increased risk for adverse pregnancy outcomes with both extremes of maternal age [5][6][7][8], some hold that the risk is not alarming particularly when pre-existing medical disorders or previous reproductive problems were controlled [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…*, P<0.05 recovery from mice 6-8 weeks old was 39.5±7.4 oocytes compared to 4.4±3.6 oocytes from mice aged 16 months [30]. Fetal growth restriction is also associated with advanced maternal age in women [3,22,23] and mares [24], and there is a higher incidence of embryonic loss and miscarriage in older women [2][3][4]12] and mares [8,11], consistent with the increased number of degenerating implantation sites in aged mice observed in this experiment. Also in agreement with our findings, maternal age in women is associated with abnormal placental growth; women of advanced maternal age have increased placental weights compared to younger women [39].…”
Section: Discussionmentioning
confidence: 98%
“…There is a potential link between maternal age and imprinting disorders, such as Angelman syndrome and Beckwith-Wiedermann syndrome, as these disorders are more prevalent in the offspring from older women [20,21]. Furthermore, maternal age has been associated with developmental abnormalities, including low birth weight in women [3,22,23] and mares [24].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women at aged 20 -29 years were chosen as the control group because pregnant women over 29 years had significant risks of diabetes mellitus, placenta previa, cesarean section, and neonatal intensive care unit (NICU) admission of the newborn [17]. Data are n (%) unless otherwise specified.…”
Section: Discussionmentioning
confidence: 99%